DESKRIPSI LIFE SKILL SISWA KELAS XI SMK-SMTI PONTIANAK PADA PROSES KIMIA INDUSTRI - Simamora, Andronikus Wp; Masriani, Masriani; Enawaty, Eny (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstrackThis study aims to describe the life skill of students of XI Industrial Chemical Skill Program which includes self-knowing, rational, social, and vocational skills of the students of grade XI SMK-SMTI Pontianak Industrial Chemical Expertise Program and to describe life skill which includes teacher's knowledge about life skill and learning life skill of class XI teacher Chemical Industry Expertise Program SMK-SMTI Pontianak. This research is a qualitative descriptive study. The subjects of this research are the students of XI Program of Chemical Industry Expertise of SMK-SMTI Pontianak and the teacher of industrial chemistry study. Data analysis technique used is qualitative descriptive analysis. Data were collected through questionnaires, observations, and interviews. The result of the research shows that students' self-knowing ability is 88,00% with very high category, rational thinking skill 73,08% with high category, 80,40% student's social skill with high category, student vocational skill is 75,50% high, knowledge of teacher to life skill equal to 81,90% with very high category, and life skill learning implementation equal to 81,70% with very high category. Thus the average life skill of students is 79.25% with very high category.Â Kata kunci: Life Skill, Self-Knowing, Thinking Rational, Social, Vocational